2001
DOI: 10.1128/jcm.39.5.1928-1931.2001
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide German Multicenter Study on the Prevalence of Antibiotic Resistance in Streptococcal Blood Isolates from Neutropenic Patients and Comparative In Vitro Activities of Quinupristin-Dalfopristin and Eight Other Antimicrobials

Abstract: In a prospective multicenter study (1996 to 1999), 156 episodes of bacteremic streptococcal infections of neutropenic patients were evaluated. Streptococcus oralis (26.3%), S. pneumoniae (26.3%), S. agalactiae (11.5%), S. mitis (9%), and S. pyogenes (5.8%) were the predominant species. Four strains (2.6%) were found to be intermediately resistant to penicillin. One strain (0.6%) was found to be highly resistant to penicillin (MIC, 8 mg/liter). Reduced susceptibility to penicillin was detected among S. oralis (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 24 publications
0
7
1
Order By: Relevance
“…The percentage of strains resistant to penicillin is seen to differ from region to region. Lower resistance rates were reported in Germany [ 19 ] compared with the rates observed in our study or that observed in the study from Spain [ 15 ]. Such geological variance has also been noted in a surveillance program that covered multiple hospitals from the United States, Canada, and Latin America [ 12 ].…”
Section: Discussioncontrasting
confidence: 87%
“…The percentage of strains resistant to penicillin is seen to differ from region to region. Lower resistance rates were reported in Germany [ 19 ] compared with the rates observed in our study or that observed in the study from Spain [ 15 ]. Such geological variance has also been noted in a surveillance program that covered multiple hospitals from the United States, Canada, and Latin America [ 12 ].…”
Section: Discussioncontrasting
confidence: 87%
“…9 Indeed, in a recent study in Germany, S. oralis and S. pneumoniae were found to be the most frequent causes of bacteremia due to viridans streptococci in neutropenic patients. 12 The ability to treat such infections is hampered by the growing resistance of the organism to a number of antibiotics, including erythromycin, tetracycline, and penicillin. 12,15 In the present study, we found that the proportion of mercury-resistant S. oralis strains isolated after placement of the mercury amalgam fillings that were resistant to erythromycin and tetracycline was 21% and 7%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Almost all streptococci studied have been found to be susceptible [14,22]. Occasionally, nonsusceptible isolates are encountered [1,2,[22][23][24][25]. In a worldwide survey for the period of 1997-2000, isolates of viridans streptococci recovered in Asia showed the lowest rate of susceptibility, at 96% [22].…”
mentioning
confidence: 99%